The Influence of the processing temperature on the microstructure of gamma-TiAl joints brazed with a Ti-15Cu-15Ni alloy - Guedes, A. (2003)
The joining of Ti-47Al-2Cr-2Nb (at.%) by diffusion brazing at 1000, 1050 and 1100ºC for 10 min, using a Ti-15Cu-15Ni (wt.%) braze alloy was investigated. The icrostructure and the chemical composition of the interfaces were studied by scanning electron microscopy (SEM) and by energy dispersive X-ray scans (EDS), respectively. The reaction between the gamma-TiAl alloy and the braze alloy led to the formation of layered interfaces, which should be essentially composed of alpha2-Ti3Al and of Ti-Ni-Cu-Al and Ti-Ni-Cu intermetallic compounds. Raising the brazing temperature increases the amount of Al rich intermetallic compounds (Ti-Ni-Cu-Al) and the extension of the interface. The increase of the thickness of the interface is primarily due to the growth of the reaction layer formed near the gamma-TiAl alloy.